iPad at work for dummies - Gruman, Galen (Hoboken, NJ : John Wiley & Sons, 2015)
If you're considering integrating the use of an iPad at work, this hands-on guide shows you step-by-step how to quickly and effectively create and interact with office documents and systems.
Introduction -- Getting started with iPad at work -- Gearing up for productivity -- Collaborating and communicating -- Accessing online resources -- Structuring and sharing documents -- The part of tens.
Includes index.
Keywords: iPad (Computer).; Business -- Data processing